Aldosterone and angiotensin II induce protein aggregation in renal proximal tubules. Issue 4 (10th September 2013) - Cheema, Muhammad U.; Poulsen, Ebbe T.; Enghild, Jan J.; Hoorn, Ewout; Fenton, Robert A.; Praetorius, Jeppe
Abstract Renal tubules are highly active transporting epithelia and are at risk of protein aggregation due to high protein turnover and/or oxidative stress. We hypothesized that the risk of aggregation was increased upon hormone stimulation and assessed the state of the intracellular protein degradation systems in the kidney from control rats and rats receiving aldosterone or angiotensin II treatment for 7 days. Control rats formed both aggresomes and autophagosomes specifically in the proximal tubules, indicating a need for these structures even under baseline conditions. Fluorescence sorted aggresomes contained various rat keratins known to be expressed in renal tubules as assessed by protein mass spectrometry. Aldosterone administration increased the abundance of the proximal tubular aggresomal protein keratin 5, the ribosomal protein RPL27, ataxin‐3, and the chaperone heat shock protein 70‐4 with no apparent change in the aggresome–autophagosome markers. Angiotensin II induced aggregation of RPL27 specifically in proximal tubules, again without apparent change in antiaggregating proteins or the aggresome–autophagosome markers. Albumin endocytosis was unaffected by the hormone administration. Taken together, we find that the renal proximal tubules display aggresome formation and autophagy. Despite an increase in aggregation‐prone protein load in these tubules during hormone treatment, renal proximal tubules seem to have sufficient capacity for removing protein aggregates from the cells.